Keragaman Jenis dan Prevalensi Lalat Pasar Tradisional di Kota Bogor (DIVERSITY AND PREVALENCE OF FLIES AT TRADITIONAL MARKETS IN BOGOR CITY) - Wahyudi, Puguh; Soviana, Susi; Hadi, Upik Kesumawati (Jurnal Veteriner; Vol 16 No 4 (2015), 2016)
Bogor city is one of the greater Jabodetabek area which has a fairly high growth of the modern market.This should not shift the role of traditional market, if accompanied with an increase in the number andquality of traditional markets, among others by controlling infestations of flies on the market that can bea vector of various diseases.This research was conducted to identify the diversity and infestation of fliesspesies in five old Bogor traditional markets. The flies were collected using insect nets and then killed withchloroform to count and identification purposes. Measuring the prevalence of flies infestation in eachmarket were using sticky fly paper on block sale of meat, fish and outside market environment. Therewere ten fly spesies belong to four main families that Calliphoridae (C. megacephala, C. saffranea, C.rufifacies, and Lucilia sericata), Muscidae (M. domestica, M. conducens, and M. fasciata), Sarcophagidae (S.haemorroidalis, and S. fuscicauda), and Drosophilidae (Drosophila repleta). The others three families werePhoridae, Anthomyiidae, and Syrphidae. Fly diversity index on each markets were 1.203 (Bogor Market),1.038 (Sukasari Market), 2.678 (Anyar Market), 1.017 (Jambu Dua Market), and 1.618 (Gunung BatuMarket). Measurement of Calliphorid flies infestations as an indicator of the presence of litterdecomposition of organic material showed a high concentration in the market environment.These resultsillustrate the general environmental sanitation of traditional markets are bad.
Keywords: Bogor; Calliphoridae; fly; Muscidae; tradisional market